A INTERNALISASI AYAT-AYAT DZIKIR DALAM LAYANAN BIMBINGAN BELAJAR UNTUK MENINGKATKAN MOTIVASI INTRINSIK SISWA: STUDI FENOMENOLOGI PSIKOSPIRITUAL - Monica Arlita; Emmi Kholilah Harahap; Rifanto Bin Ridwan (STKIP Subang, 2026)
This study aims to explore in depth the lived experiences of students regarding how guidance and learning activities based on the Qur’anic verses of dzikir reconstruct their awareness and enhance their intrinsic learning motivation. This research employed a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design. The participants consisted of eight eleventh-grade students. The findings identified three major themes: (1) Transcendental Intention Reorientation; (2) Cognitive Thuma’ninah; and (3) Ulul Albab Academic Resilience. The study concludes that the integration of dzikir verses significantly transforms the cognitive and affective landscape of students’ learning awareness.